Genomic analysis and characterization of phages infecting the marine Roseobacter CHAB-I-5 lineage reveal a globally distributed and abundant phage genus - Zhang, Zefeng; Wu, Zuqing; Liu, He; Yang, Mingyu; Wang, Rui; Zhao, Yanlin; Chen, Feng (Frontiers in Microbiology, 2023)
Marine phages play an important role in marine biogeochemical cycles by regulating the death, physiological metabolism, and evolutionary trajectory of bacteria. The Roseobacter clade is an abundant and important heterotrophic bacterial group in the ocean, and plays an important role in carbon, nitrogen, sulfur and phosphorus cycling. The CHAB-I-5 lineage is one of the most dominant Roseobacter lineages, but remains largely uncultured. Phages infecting CHAB-I-5 bacteria have not yet been investigated due to the lack of culturable CHAB-I-5 strains. In this study, we isolated and sequenced two new phages (CRP-901 and CRP-902) infecting the CHAB-I-5 strain FZCC0083. The two phages are highly similar, with an average nucleotide identity of 89.17%, and sharing 77% of their open reading frames. We identified several genes involved in DNA replication and metabolism, virion structure, DNA packing and host lysis from their genomes. Metagenomic mining identified 24 metagenomic viral genomes closely related to CRP-901 and CRP-902. Genomic comparison and phylogenetic analysis demonstrated that these phages are distinct from other known viruses, representing a novel genus-level phage group (CRP-901-type). The CRP-901-type phages do not contain DNA primase and DNA polymerase genes, but a novel bifunctional DNA primase-polymerase gene with both primase and polymerase activities was identified in most of these phages. Read mapping analysis showed that the CRP-901-type phages are widespread across the world’s oceans and are most abundant in estuarine and polar waters. Their abundance is generally higher than other known roseophages and even higher than most pelagiphages in the polar region. In summary, this study has greatly expanded our understanding of the genetic diversity, evolution, and distribution of roseophages. Our analysis suggests that the CRP-901-type phage is an important and novel marine phage group that plays important roles in the physiology and ecology of roseobacters.